Language Technologies for the Challenges of the Digital Age 27th International Conference, GSCL 2017, Berlin, Germany, September 13-14, 2017, Proceedings - Rehm, Georg; Declerck, Thierry (Lecture Notes in Artificial Intelligence,, 2018)
This open access volume constitutes the refereed proceedings of the 27th biennial conference of the German Society for Computational Linguistics and Language Technology, GSCL 2017, held in Berlin, Germany, in September 2017, which focused on language technologies for the digital age. The 16 full papers and 10 short papers included in the proceedings were carefully selected from 36 submissions. Topics covered include text processing of the German language, online media and online content, semantics and reasoning, sentiment analysis, and semantic web description languages.